MENGUNGKAP PERAN MANAJEMEN LABA SERTA RASIO KEUANGAN PADA DINAMIKA NILAI SAHAM : DIBALIK ANGKA - Muhamat Akhrom (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
The aim of this research is to explore the influence of TATO, ROA and EPS ratios on company share prices, as well as to explore the moderating effect of earnings management. This research focuses on companies in the property and real estate sectors listed on the Indonesia Stock Exchange in the period 2021 to 2024. Through moderated regression analysis, it was found that the EPS ratio has a significant impact on company share prices, this influence is even stronger when moderated. by earnings management. Meanwhile, other variables do not show the same influence. This finding enriches our understanding that investors tend to prioritize potential investment returns, rather than just operational efficiency